Bioconversion of poly (vinylalcohol) -PVOH- to vanillin in a Phanerochaete chrysosporium culture medium (2003)
ABSTRACT: The bioconversion of Phanerochaete chryso-sporium cultures in aqueous poly(vinyl alcohol) – PVAL– solutions was studied. A 50% weight loss was observed within 20 days, caused by a ligninperoxidase – LiP –enzyme which is produced during the secondary metabolism of Phanerochaete chrysosporium. The changes of the chemical structure of PVAL were studied by UV- and IR-spectroscopy. The presence of vanillin – the major metabolic reaction product, benzaldehyde, and veratry-lalcohol was determined chromatographically (HPLC) in the extra cellular medium after different reaction times. A possible mechanism of the biological degradation is outlined.